Vibration Isolation of a Rubber-Concrete Alternating Superposition In-Filled Trench for Train-Induced Environmental Vibration Based on 2.5D Indirect Boundary Element Method - Liguo Jin (Frontiers Media S.A., 2021)
A new train-induced vibration isolation measure of rubber-concrete alternating superposition in-filled trench is presented in this paper. For analyzing the vibration isolation effect of the new measure, this paper establishes a 2.5D train-track-layered foundation-filled trench model to analyze the dynamics of track and layered foundation with the in-filled trench. The correctness of the model is verified by using the measured data of the Sweden X-2000 high-speed train. The vibration isolation effect of the rubber-concrete alternating superposition in-filled trench is calculated by using the actual soft soil foundation parameters of the X-2000 high-speed train, and the vibration isolation effect is also compared with that of the empty trench, rubber in-filled trench, and concrete in-filled trench. The results show that the vibration isolation effect of the rubber-concrete alternating superposition in-filled trench proposed in this paper is better than that of the C30 concrete in-filled trench, especially the impact on displacement. Compared with low-frequency vibrations generated by the lower train speed, the rubber-concrete alternating superposition in-filled trench has a better vibration isolation effect on high-frequency vibrations caused by higher-speed trains. The rubber-concrete alternately superposition in-filled trench has the frequency band characteristics of elastic waves. Elastic waves in the passband frequency range can propagate without attenuation, while the elastic waves in the forbidden frequency range will be filtered out.